POS0112 DEUCRAVACITINIB REDUCES INTERFERONS, B-CELL PATHWAYS, AND SEROLOGICAL BIOMARKERS OF SYSTEMIC LUPUS DISEASE ACTIVITY: PHARMACODYNAMIC ANALYSIS FROM THE PHASE 2 PAISLEY STUDY - Kahlenberg, J. M.; Sanz, I.; Wu, C.; Hu, Y.; Kim, J. H.; Singhal, S.; Catlett, I. M. (Annals of the rheumatic diseases, 2023)
BackgroundTyrosine kinase 2 (TYK2) mediates signaling of key cytokines (eg, type 1 IFNs, IL-23, and IL-12) involved in systemic lupus erythematosus (SLE) pathogenesis. Deucravacitinib is a first-in-class, oral, selective, allosteric TYK2 inhibitor approved in multiple countries for the treatment of adults with plaque psoriasis.[1,2] Deucravacitinib demonstrated a favorable safety and efficacy profile in a phase 2 trial in patients with psoriatic arthritis[3] and a phase 2 trial in patients with active SLE (PAISLEY; NCT03252587).[4]ObjectivesThis analysis evaluated the effect of deucravacitinib on biomarkers of TYK2-mediated pathways, B-cell pathways, and serological biomarkers in patients in the phase 2 PAISLEY SLE trial.MethodsThe 48-week PAISLEY trial randomized 363 patients with SLE 1:1:1:1 to placebo or deucravacitinib 3 mg twice daily (BID), 6 mg BID, or 12 mg once daily (QD). Whole blood transcripts, serum proteins, blood cell subsets, and antibody profiles at screening and baseline through week 48 were measured by immunoassays and flow cytometry. In a substudy, samples were collected from 83 subjects 22 to 114 hours after the initial dose. Samples from demographically matched healthy subjects were collected and measured for comparison.ResultsAt screening, 42 genes/modules and 75 proteins were differentially expressed compared with healthy subjects, with fold change >1.5 and adjusted P value <0.05. With deucravacitinib treatment, significant reductions were observed in IFNα (at week 48) and IFNλ (week 2 through week 48), and IFNγ was numerically lower after week 12. Deucravacitinib significantly inhibited IFN-regulated gene (IRG) expression from week 4 through week 44 (Figure 1). Deucravacitinib, but not placebo, reduced expression of cytokines and chemokines downstream of IFN activity, including BAFF, CXCL10, and MCP2. Adjusted mean percent changes from baseline at week 48 after treatment with deucravacitinib 3 mg BID, 6 mg BID, or 12 mg QD were –26%, –31%, and –30% for MCP2 and –42%, –43%, and –48% for CXCL10, respectively. Selected cytokines and chemokines including IFNλ, CXCL10, CCL19, and MCP2 were significantly reduced in the BID-dosed arms as early as 2 to 3 days after dose initiation. With deucravacitinib treatment, lymphocyte and neutrophil counts and complement levels increased, while markers associated with B-cell activation and differentiation including BLC (CXCL13), CD38 (gene expression), and autoantibodies were reduced.ConclusionDeucravacitinib suppressed IFN production, IRG expression, IFN-inducible proteins, B-cell pathway markers, and serological biomarkers, consistent with clinical symptom improvements in SLE patients treated with deucravacitinib. Suppression of both IFN and B-cell pathways suggests a broad reduction in lupus pathophysiology. These results provide a molecular framework for understanding how deucravacitinib modifies molecular networks in SLE and support the continued investigation of deucravacitinib as a treatment for SLE in phase 3 trials.References[1]Armstrong A, et al. J Am Acad Dermatol. 2023;88(1):29-39.[2]Strober B, et al. J Am Acad Dermatol. 2023;88(1):40-51.[3]Mease PJ, et al. Ann Rheum Dis. 2022;81:815-822.[4]Morand E, et al. Arthritis Rheumatol. 2022; Nov 11 (Epub ahead of print).AcknowledgementsThis clinical trial was sponsored by Bristol Myers Squibb.Disclosure of InterestsJ Michelle Kahlenberg Consultant of: Q32 Bio, Celgene/Bristol Myers Squibb, Ventus Therapeutics, Rome Therapeutics, and Janssen, AstraZeneca, Eli Lilly, GlaxoSmithKline, Bristol Myers Squibb, Avion Pharmaceuticals, Provention Bio, Aurinia Pharmaceuticals, Ventus Therapeutics, and Boehringer Ingelheim., Ignacio Sanz Shareholder of: Kyverna, Consultant of: Exagen, Bristol Myers Squibb, Celgene, GlaxoSmithKline, Janssen, Kyverna, and Visterra, Chun Wu Shareholder of: Bristol Myers Squibb, Employee of: Bristol Myers Squibb, Yanhua Hu Shareholder of: Bristol Myers Squibb, Employee of: Bristol Myers Squibb, Jin Hyang Kim Shareholder of: Bristol Myers Squibb, Employee of: Bristol Myers Squibb, Shalabh Singhal Shareholder of: Bristol Myers Squibb, Employee of: Bristol Myers Squibb, Ian M. Catlett Shareholder of: Bristol Myers Squibb, Employee of: Bristol Myers Squibb.